Photocatalytic hydrogen production using bench-scale trapezoidal photocatalytic reactor. (6th March 2020) - Anthony Raja, M.; Preethi, V.
Abstract: Hydrogen is the future fuel and energy carrier, which has numerous applications. During combustion, produces only water vapour instead of greenhouse gas emissions. Photocatalytic production of hydrogen as a clean fuel from sulphide wastewater arises as a necessary option that must be considered. Here we report the performance of CNT added CdZnS/Fe2 O3 for hydrogen recovery from highly toxic sulphide containing wastewater. The prepared photocatalysts were characterised for XRD (structure), UV-DRS (band gap), HRTEM (particle size), XPS (binding energy), SEM (morphology) and ICP (elemental composition). The photocatalytic hydrogen recovery was performed using novel trapezoidal photocatalytic reactor. The synthesized novel CNT - CdZnS/Fe2 O3 nano-photocatalyst has highest production of hydrogen (2679 μmol/h) than plain CdZnS/Fe2 O3 (2009 μmol/h).The feasibility studies were conducted to optimize the operating variables viz., S 2- (sulphide ion) concentrations, SO3 2- (sulphite ion) concentrations, catalyst amount, light irradiation and volume of wastewater. Reusability studies under natural solar irradiation were performed and the CNT deposited CdZnS/Fe2 O3 photocatalyst was found to be stable upto seven runs. Graphical abstract: Image 1 Highlights: CNT doped CdZnS/Fe2 O3 was synthesized by coprecipitation and ceramic methods. Trapezoidal photocatalytic reactor of 4 L capacity was developed. Optimization studies were conducted under visible light irradiation. With artificial visible lamp, CNT doped CdZnS/Fe2 O3 gives 60 mL at Q.Y. 23.5%. Direct solar study was conducted and achieved 450 mL/h at Q.Y. 88%.